Application of Interfacial Propagation and Kinking Crack Concept to ECC/Concrete Overlay Repair System - Yaw ChiaHwan; Li Wei (Advances in Materials Science and Engineering)
Research on the application of ultraductile engineered cementitious composite (ECC) as overlay in the repair of deteriorated concrete structures is performed in this paper. Also, interfacial crack kinking and trapping mechanism experimentally observed in ECC/concrete overlay repair system are described by comparison of toughness and energy release rate. The mechanism involves cycles of extension, kinking, and arrest of interfacial crack into the overlay. Experimental testing of overlay repair system reveals significant improvements in load carrying capacity and ductility over conventional concrete overlay. The commonly observed overlay system failure mode of delamination or spalling is eliminated when ECC is applied. These failure modes are suppressed when ECC is used as an ideal and durable candidate overlay repair material.